PENDEKATAN MATEMATIS DALAM PENENTUAN WAKTU EFEKTIF PERTUMBUHAN TANAMAN CABAI MERAH - SURYAWARDHANI, N.W. (Agrotrop : Journal on Agriculture Science; Vol 1 No 1 (2011))
Mathematical Model in Determining Effective Time for Growth Rate of Red Chili The growth rate showed a sigmoidal shaped pattern with initially slow growth rate and speeding up till a certain period before slowing down to approach a limit. So it is very important to define the plant growth model. The aim of the study is to estimate the effective time of plant growth by looking at the mathematical model. The statistical analysis showed that the growth ofCapsium annum Cult. Hot Beauty’s can be fit well by Janoscheck model and the effective growth time occurs as the plant is in the interval of 14 to 21 days after transplanting.
Keywords: Janoschek model, growth rate